Ventricular standstill during lumbar surgery in the prone position. Issue 2 (7th July 2013) - Windsor, David; D'Agapeyeff, Alex
Summary: We describe a case of ventricular standstill during elective lumbar surgery. On each occasion the episodes appeared to be related to dural traction. A literature search suggested this was a rare but significant event. A neurological mechanism for such events is discussed.